Evaluating a Dry vs. Wet Disinfection in Boot Baths on Detection of Porcine Epidemic Diarrhea Virus and Porcine Reproductive and Respiratory Syndrome Virus RNA - Olivia L. Harrison; Grace E. Houston; Allison K. Blomme; Haley K. Otott; Jianfa Bai; Elizabeth G. Poulsen Porter; Jason C. Woodworth; Chad B. Paulk; Jordan T. Gebhardt; Cassandra K. Jones (Kansas Agricultural Experiment Station Research Reports, 2022)
Maintaining biosecurity between swine barns is challenging, and boot baths are an easily implementable option some utilize to limit pathogen spread. However, there are concerns regarding their efficacy, especially when comparing wet or dry disinfectants. The objective of this study was to evaluate the efficacy of boot baths in reducing the quantity of detectable porcine epidemic diarrhea virus (PEDV) and porcine reproductive and respiratory syndrome virus (PRRSV) genetic material using wet or dry disinfectants. Treatments included 1) control; 2) dry chlorine powder (Traffic C.O.P., PSP, LLC, Rainsville, AL); and 3) wet quaternary ammonium/glutaraldehyde liquid (1:256 Synergize, Neogen, Lexington, KY). Prior to disinfection, rubber boots were inoculated with 1 mL of co-inoculants of PRRSV (1×105TCID50/mL) and PEDV (1×105TCID50/mL) and dried for 15 min. After the drying period, a researcher placed the boot on the right foot and stepped directly on a stainless steel coupon (control). Alternatively, the researcher stepped first into a boot bath containing either the wet or dry sanitizer, stood for 3 s, and then stepped onto a steel coupon. After one min, an environmental swab was then collected and processed from each boot and steel coupon. The procedure was replicated 12 times per disinfectant treatment. Samples were analyzed using a duplex qPCR at the Kansas State Veterinary Diagnostic Laboratory. Cycle threshold values, which indicate the presence or absence of the inoculants and their relative concentrations when present, were analyzed using SAS GLIMMIX (v. 9.4, SAS Institute, Inc., Cary, NC). There was no evidence of a disinfectant × surface × virus interaction (P>0.10). An interaction between disinfectant × surface impacted (P<0.05) the quantity of detectable viral RNA. As expected, the quantity of the viruses on the coupon were greatest in the control, indicating that a contaminated boot has the ability to transfer viruses from a contaminated surface to a clean surface. Comparatively, the dry disinfectant treatment resulted in no detectable viral RNA on either the boot or subsequent coupon. The wet disinfectant treatment had statistically similar (P>0.05) viral contamination to the control on the boot, but less viral contamination compared to the control on the metal coupon. In this experiment, a boot bath with dry powder was the most efficacious in reducing the detectable viral RNA on both boots and subsequent surfaces.
Keywords: boot bath; PEDV; PRRSV; swine